KARAKTERISTIK GANGGUAN NYERI SEBAGAI GEJALA NONMOTORIK PADA PENYAKIT PARKINSON - Vincent Ongko Wijaya,* Rizaldy Taslim Pinzon* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION PARKINSONS DISEASE PD AS A PROGRESSIVE NEURODEGENERATIVE DISORDER OF THE CENTRAL NERVOUS SYSTEM THAT HAS MOTOR AND NONMOTOR SYMPTOM PAIN IS ONE OF THE MOST COMMON NONMOTOR SYMPTOM OF PD AND HAS A SIGNIFICANT IMPACT IN IMPAIRMENT OF PATIENTS QUALITY OF LIFE THEREFORE UNDERSTANDING THE CHARACTERISTICS OF PAIN IN PD IS NEEDED